Solid electrolyte and all-solid-state battery
The development of a specific solid electrolyte composition with optimized compositional ratios and X-ray diffraction patterns addresses the challenge of improving initial charge and discharge efficiency in all-solid-state batteries, resulting in enhanced performance and reliability.
Patent Information
- Application Number
- JP2023164154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
All-solid-state batteries using halide-based solid electrolytes face challenges in improving initial charge and discharge efficiency.
A solid electrolyte composition of AaAlbZr1-b+αGcOdXe is developed, where A includes Li, K, or Na, G includes various metals, X includes halides, and specific compositional ratios and X-ray diffraction patterns are optimized to enhance ionic conductivity and reduction resistance.
The proposed solid electrolyte significantly increases the initial charge and discharge efficiency of all-solid-state batteries by improving ionic conductivity and reduction resistance, leading to better performance and reliability.
Smart Images

Figure 2025054920000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte and an all-solid-state battery. [Background technology]
[0002] In recent years, electronics technology has developed remarkably, and portable electronic devices have become smaller, lighter, thinner, and more multifunctional. There is a strong demand for batteries, which serve as the power source for electronic devices, to be smaller, lighter, thinner, and more reliable. For this reason, all-solid-state batteries that use solid electrolytes as electrolytes have attracted attention. Known solid electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, and halide-based solid electrolytes.
[0003] For example, Patent Document 1 states: 2+a E 1-b+α G b D c X d The present invention discloses a halide-based solid electrolyte represented by the formula: [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2021 / 024785 Summary of the Invention [Problem to be solved by the invention]
[0005] Halide-based solid electrolytes are said to have higher ionic conductivity than oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes, etc. On the other hand, there is a demand for improved initial charge / discharge efficiency in all-solid-state batteries that use halide-based solid electrolytes.
[0006] The present disclosure has been made in consideration of the above problems, and has an object to provide a solid electrolyte that can improve the initial charge / discharge efficiency of an all-solid-state battery. [Means for solving the problem]
[0007] To solve the above problems, the following means are provided.
[0008] The solid electrolyte according to the first aspect is A a Al b Zr 1-b+α G c O d X e ···(1). In formula (1), A is any one or more selected from the group consisting of Li, K, and Na; G is any one or more selected from the group consisting of Mg, Ca, Sr, Ba, Y, Yb, Sc, La, Ce, Hf, Ta, W, and Nb; X is any one or more selected from the group consisting of F, Cl, Br, and I; a satisfies 0.1 < a < 2 + b + β; b satisfies 0.1 ≤ b ≤ 0.9; c satisfies 0 ≤ c < 0.5; d satisfies 0.01 < d < 3; e satisfies 2.5 < e < 6.1; α satisfies -0.5 < α < 0.3; β is -c when G is a pentavalent element and b > c + 0.01, 0 when G is a tetravalent element or does not contain G, c when G is a trivalent element, and 2c when G is a divalent element. The solid electrolyte according to the first aspect has an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays that satisfies the first condition or the second condition. The first condition is that both the first intensity ratio obtained by dividing the second intensity by the first intensity and the second intensity ratio obtained by dividing the second intensity by the third intensity are 2.0 or less. The first intensity is the maximum diffraction intensity in the first range of diffraction angle 29.5° ± 0.5°; the second intensity is the maximum diffraction intensity in the second range of diffraction angle 31.9° ± 0.5°; the third intensity is the maximum diffraction intensity in the third range of diffraction angle 34.6° ± 0.5°. The second condition is that there are no peaks in the first range, the second range, and the third range.
[0009] In the formula (1) of the solid electrolyte according to the above aspect, X may contain Cl.
[0010] In the formula (1) of the solid electrolyte according to the above aspect, X may contain any one or more selected from the group consisting of Cl, F, Br, and I.
[0011] In the formula (1) of the solid electrolyte according to the above aspect, X may be Cl.
[0012] In the formula (1) of the solid electrolyte according to the above aspect, A may be Li.
[0013] In the formula (1) of the solid electrolyte according to the above aspect, A may be Na.
[0014] In the formula (1) of the solid electrolyte according to the above aspect, a may satisfy 0.5 < a < 2 + b + β.
[0015] In the formula (1) of the solid electrolyte according to the above aspect, b may satisfy 0.3 ≤ b ≤ 0.7, and 1 + α + c may satisfy 0.8 < 1 + α + c < 1.2.
[0016] In the formula (1) of the solid electrolyte according to the above aspect, c may satisfy 0 ≤ c ≤ 0.3.
[0017] The solid electrolyte according to the above aspect may further contain oxide particles. The particle size of the oxide particles is 5.0 μm or less.
[0018] The all-solid-state battery according to the second aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the negative electrode contains the solid electrolyte according to the above aspect.
[0019] The all-solid-state battery according to the third aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the solid electrolyte layer contains the solid electrolyte according to the above aspect.
[0020] The all-solid-state battery according to the fourth aspect includes a positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, and the positive electrode contains the solid electrolyte according to the above aspect. Effect of the Invention
[0021] The solid electrolyte according to the above embodiment can improve the initial charge / discharge efficiency of an all-solid-state battery. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present embodiment will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.
[0024] "Solid electrolyte" A solid electrolyte is a material that can move ions when an external electric field is applied. Solid electrolytes can be used as part of the solid electrolyte layer and electrode components of solid-state batteries.
[0025] The solid electrolyte according to this embodiment is A a Al b Zr 1-b+α G c O d X e The solid electrolyte contains a compound represented by the formula (1). In addition to the compound, the solid electrolyte may contain unavoidable impurities, materials derived from raw materials, and the like.
[0026] In formula (1), A is any one or more selected from the group consisting of Li, K, and Na; G is any one or more selected from the group consisting of Mg, Ca, Sr, Ba, Y, Yb, Sc, La, Ce, Hf, Ta, W, and Nb; X is any one or more selected from the group consisting of F, Cl, Br, and I; a satisfies 0.1 < a < 2 + b + β; b satisfies 0.1 ≤ b ≤ 0.9; c satisfies 0 ≤ c < 0.5; d satisfies 0.01 < d < 3; e satisfies 2.5 < e < 6.1; α satisfies -0.5 < α < 0.3; β is -c when G is a pentavalent element and b > c + 0.01, β is 0 when G is a tetravalent element or does not contain G, β is c when G is a trivalent element, and β is 2c when G is a divalent element.
[0027] Here, whether the solid electrolyte contains the compound of formula (1) can be confirmed by elemental mapping analysis using energy-dispersive X-ray spectroscopy (TEM-EDX). In elemental mapping, when each constituent element is in a uniform dispersion state, it can be regarded that the compound represented by formula (1) is synthesized. Note that "each constituent element is in a uniform dispersion state" means that no distinct aggregation state is confirmed in elemental mapping.
[0028] The solid electrolyte may be in the state of powder (particles) or in the state of a sintered body obtained by sintering the powder. The solid electrolyte may also be a molded body formed by compressing the powder, a molded body formed by molding a mixture of the powder and a binder, or a coating film formed by applying a paint containing the powder, the binder, and a solvent and then heating to remove the solvent. Also, the main structure of the solid electrolyte may be amorphous or crystalline.
[0029] In formula (1), A is any one or more selected from the group consisting of Li, K, and Na. It is preferable that A is Li or Na. A solid electrolyte in which A is Li or Na has high ionic conductivity.
[0030] a represents the composition ratio of A in the compound represented by formula (1). In formula (1), a satisfies 0.1 < a < 2 + b + β. In formula (1), a may satisfy 0.5 < a < 2 + b + β. A solid electrolyte with an appropriate content of Li in the compound has high ionic conductivity. Also, a all-solid-state battery using a solid electrolyte with an appropriate content of Li has high initial charge-discharge efficiency. This is considered to be because an appropriate SEI film is formed due to the appropriate content of Li. A thin and appropriate SEI film inhibits electron conduction but does not inhibit ionic conduction. By inhibiting electron conduction, the reduction resistance of the solid electrolyte is improved, and the initial charge-discharge efficiency of the all-solid-state battery is increased. By having high ionic conductivity of the SEI film, the ionic conductivity of the solid electrolyte is increased. b represents the composition ratio of Al in formula (1).
[0031] β is a value that varies depending on G in formula (1). When the chemical formula represented by formula (1) does not contain G (i.e., c = 0), β = 0. When the chemical formula represented by formula (1) contains G, β varies depending on the valence of G. When G is a pentavalent element, β = -c. Also, when G is a pentavalent element, b > c + 0.01 is satisfied. When G is a tetravalent element, β = 0. When G is a trivalent element, β = c. When G is a divalent element, β = 2c. c represents the composition ratio of G in formula (1).
[0032] The compound represented by formula (1) contains Al (aluminum) as an essential atom. Al is substituted for a part of Zr that forms the skeleton of the solid electrolyte. Al has a lower reduction potential than Zr. A solid electrolyte in which a part of Zr is substituted with Al has a wide potential window and enhanced reduction resistance.
[0033] b represents the composition ratio of Al in the compound represented by formula (1). In formula (1), b satisfies 0.1 ≤ b ≤ 0.9. In formula (1), b may satisfy 0.3 ≤ b ≤ 0.7. If the substitution amount of Al is small, the reduction resistance of the solid electrolyte decreases, and if the substitution amount of Al is too large, the ionic conductivity tends to decrease.
[0034] The compound represented by formula (1) contains Zr (zirconium) as an essential atom. Zr is an atom that forms part of the skeleton of the solid electrolyte. The composition ratio of Zr is represented by 1 - b + α.
[0035] α satisfies -0.5 < α < 0.3. When the value of α varies, the ratio of Zr to A in formula (1) changes. A solid electrolyte in which the ratio of Zr to A in formula (1) is within an appropriate range has high ionic conductivity. α may satisfy -0.3 < α < 0.3, preferably satisfies -0.2 < α < 0.2, and more preferably satisfies -0.1 < α < 0.1.
[0036] The compound represented by formula (1) may contain an atom represented by G. The compound represented by formula (1) may not contain an atom represented by G. When the compound represented by formula (1) contains an atom represented by G, G is substituted for a part of Zr that forms the skeleton of the solid electrolyte. G is any one or more selected from the group consisting of Mg, Ca, Sr, Ba, Y, Yb, Sc, La, Ce, Hf, Ta, W, and Nb.
[0037] c represents the composition ratio of G in the compound represented by formula (1). In formula (1), c satisfies 0 ≦ c < 0.5. When c = 0, it means that the compound represented by formula (1) does not contain G. In formula (1), c may satisfy 0 ≦ c ≦ 0.3, and preferably may satisfy 0 ≦ c ≦ 0.2. If the substitution amount of G is too large, the ionic conductivity of the solid electrolyte tends to decrease. Also, it is preferable that 1 + α + c satisfies 0.8 < 1 + α + c < 1.2. A solid electrolyte in which 1 + α + c satisfies this range has high ionic conductivity.
[0038] The compound represented by formula (1) contains O (oxygen) as an essential atom. d represents the composition ratio of O in the compound represented by formula (1). d satisfies 0.01 < d < 3.0. d may satisfy 0.3 < d < 2.0. A solid electrolyte containing O within an appropriate range has high ionic conductivity. When d exceeds 3.0, the ionic conductivity of the solid electrolyte tends to decrease.
[0039] The compound represented by formula (1) contains a halide atom represented by X. X is an essential atom for the solid electrolyte. X is any one or more selected from the group consisting of F, Cl, Br, and I. Preferably, X contains Cl. X may contain Cl and any one or more selected from the group consisting of F, Br, and I. Also, X may be Cl.
[0040] When X contains any one or more selected from the group consisting of Cl and F, Br, and I, formula (1) is rewritten as A a Al b Zr 1-b+α G c O d (ClX1) e ···(2). In formula (2), e is the composition ratio as the total of Cl and X1. X1 is any one selected from the group consisting of F, Br, and I. When X is Cl, formula (1) is rewritten as A a Al b Zr 1-b+α G c O d Cl e ···(3).
[0041] When X contains F, the ionic conductivity of the solid electrolyte increases and the oxidation resistance increases. When X contains Cl, the ionic conductivity of the solid electrolyte increases, the oxidation resistance increases, and a well-balanced solid electrolyte is obtained. When X contains Br, the ionic conductivity of the solid electrolyte increases, the oxidation resistance increases, and a well-balanced solid electrolyte is obtained. When X contains I, the ionic conductivity of the solid electrolyte increases.
[0042] e represents the composition ratio of X in the compound represented by formula (1). e satisfies 2.5 < e < 6.1. e may satisfy 2.5 < e < 5.4. A solid electrolyte in which the content of X contained in the compound is within an appropriate range has high ionic conductivity. Also, when X is sufficiently contained in the solid electrolyte, it becomes easy to form pellets having sufficient strength.
[0043] The composition analysis of the solid electrolyte is performed, for example, by surface analysis using an electron probe microanalyzer (EPMA), etc. The composition analysis may also be performed, for example, by energy dispersive X-ray spectroscopy using a transmission electron microscope (SEM-EDS) or inductively coupled plasma mass spectrometry (ICP-MS).
[0044] The X-ray diffraction pattern obtained by measuring the solid electrolyte according to this embodiment by X-ray diffraction using Cu-Kα radiation satisfies the first or second condition.
[0045] The first condition is that a first intensity ratio obtained by dividing the second intensity by the first intensity and a second intensity ratio obtained by dividing the second intensity by the third intensity are both 2.0 or less. Here, the first intensity is the maximum diffraction intensity in a first range of a diffraction angle of 29.5°±0.5°. The second intensity is the maximum diffraction intensity in a second range of a diffraction angle of 31.9°±0.5°. The third intensity is the maximum diffraction intensity in a third range of a diffraction angle of 34.6°±0.5°. It is preferable that the first intensity ratio obtained by dividing the second intensity by the first intensity and the second intensity ratio obtained by dividing the second intensity by the third intensity are both 1.0 or less. The second intensity may be zero.
[0046] The second condition is that there is no significant peak in any of the above-mentioned ranges 1, 2, and 3. The significant peak means a peak that is confirmed even when the measurement data is filtered using, for example, a Fourier transform to remove noise.
[0047] When the first condition is satisfied, the X-ray diffraction pattern has at least a peak in any one of the first range, the second range, or the third range, and when the second condition is satisfied, the X-ray diffraction pattern has no peak in any of the first range, the second range, or the third range.
[0048] The X-ray diffraction pattern evaluates the crystal structure of the solid electrolyte. Although the cause is not clear, if the X-ray diffraction pattern of the solid electrolyte meets any of these conditions, the reduction resistance of the solid electrolyte is improved.
[0049] The solid electrolyte may contain oxide particles in addition to the compound represented by formula (1). The oxide particles may be, for example, an oxide of A, ZrO 2 The oxide particles are preferably oxides of A and G. The oxide particles are preferably oxides of A. The abundance ratio of the oxide particles is, for example, 0.1 mass % or more and 1.0 mass % or less in terms of mass ratio with respect to the entire solid electrolyte. The particle diameter of the oxide particles is preferably 5.0 μm or less, and more preferably 4.0 μm or less.
[0050] The presence or absence of oxide particles in the solid electrolyte can be confirmed by, for example, surface analysis using an electron probe microanalyzer (EPMA), energy dispersive X-ray spectroscopy using a transmission electron microscope (SEM-EDS), inductively coupled plasma mass spectrometry (ICP-MS), etc.
[0051] When a solid electrolyte contains a small amount of oxide particles, the ionic conductivity of the solid electrolyte is improved. The reason for this is not clear, but it is thought that the oxide particles act as a conductive path for ions between the compounds represented by formula (1) and assist the ionic conduction between the compounds. When oxide particles are present in a solid electrolyte, the grain boundary resistance between the compounds represented by formula (1) decreases, improving the ionic conductivity of the solid electrolyte as a whole.
[0052] (Method of manufacturing solid electrolyte) When the solid electrolyte is in a powder state, it can be prepared, for example, by a mechanochemical method. For example, raw material powders containing predetermined elements in a predetermined molar ratio are mixed and reacted. The rotation speed and mixing time when mixing the raw material powders are parameters that affect the XRD pattern of the solid electrolyte. The rotation speed or mixing time of the mechanochemical reaction is adjusted so that the XRD pattern satisfies the above-mentioned first condition or second condition. It is preferable to confirm the rotation speed or mixing time of the mechanochemical reaction that satisfies the first condition or the second condition by setting conditions in advance.
[0053] When the raw material powder contains a halide raw material, the halide raw material is likely to evaporate when the temperature is increased. The halogen gas may be made to coexist in the atmosphere during sintering to supplement the halogen. In addition, when the raw material powder contains a halide raw material, sintering may be performed by a hot press method using a mold with high airtightness. In this case, since the mold has high airtightness, evaporation of the halide raw material due to sintering can be suppressed. By sintering in this manner, a solid electrolyte in the form of a sintered body made of a compound having a predetermined composition is obtained.
[0054] In the manufacturing process of the solid electrolyte, heat treatment may be performed as necessary. By performing heat treatment, the crystallite size of the solid electrolyte can be adjusted. For example, in an argon gas atmosphere, heat treatment is preferably performed at a temperature of 130°C to 650°C for 0.5 hours to 60 hours, and more preferably at a temperature of 175°C to 600°C for 1 hour to 30 hours. By performing heat treatment in an argon gas atmosphere at a temperature of 150°C to 550°C for 5 hours to 24 hours, the crystallite size of the solid electrolyte can be set to 5 nm to 500 nm.
[0055] When the solid electrolyte contains oxide particles, the oxide particles may be mixed as an additive after the solid electrolyte is synthesized. Also, if a two-stage synthesis method is used to prepare a solid electrolyte, the oxide particles tend to remain in the solid electrolyte. The two-stage synthesis method is a synthesis method in which a lithium compound and a zirconium compound are reacted first, and then an aluminum compound is reacted. In the one-stage synthesis method, a lithium compound, a zirconium compound, and an aluminum compound are reacted at the same time.
[0056] In the solid electrolyte according to the present embodiment, a part of Zr is replaced by Al, and the initial charge-discharge efficiency is high. This is believed to be because the reduction potential of Al is lower than that of Zr. It is believed that the reduction resistance of the solid electrolyte is improved by replacing a part of Zr with Al.
[0057] [All-solid battery] Fig. 1 is a cross-sectional schematic diagram of an all-solid-state battery according to this embodiment. The all-solid-state battery 10 shown in Fig. 1 includes a positive electrode 1, a negative electrode 2, and a solid electrolyte layer 3. The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. The above-mentioned solid electrolyte may be included in the solid electrolyte layer 3, or may be included in the positive electrode 1 or the negative electrode 2, or may be included in both of them. The positive electrode 1 and the negative electrode 2 are connected to external terminals (not shown) and are electrically connected to the outside.
[0058] The all-solid-state battery 10 charges or discharges by transferring ions between the positive electrode 1 and the negative electrode 2 via the solid electrolyte layer 3, and transferring electrons via an external circuit. The all-solid-state battery 10 may be a laminate in which the positive electrode 1, the negative electrode 2, and the solid electrolyte layer 3 are laminated, or may be a wound body in which the laminate is wound. The all-solid-state battery is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, and the like.
[0059] <Solid electrolyte layer> The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. The solid electrolyte layer 3 includes a solid electrolyte that can move ions by an externally applied voltage. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.
[0060] The solid electrolyte layer 3 is, for example, a halide-based solid electrolyte. The solid electrolyte layer 3 includes, for example, the above-mentioned solid electrolyte. When the above-mentioned solid electrolyte is included in the positive electrode 1 or the negative electrode 2, the solid electrolyte included in the solid electrolyte layer 3 does not have to be the above-mentioned one.
[0061] The solid electrolyte layer 3 may contain, in addition to the solid electrolyte, a binder, a compound, etc. The binder may be the same as that used in the positive electrode 1 or the negative electrode 2. The compound is a material originating from the raw material powder.
[0062] <Positive electrode> 1, the positive electrode 1 has a plate-like (foil-like) positive electrode current collector 1A and a positive electrode mixture layer 1B. The positive electrode mixture layer 1B is in contact with at least one surface of the positive electrode current collector 1A.
[0063] "Positive electrode current collector" The positive electrode current collector 1A may be made of any electronically conductive material that is resistant to oxidation during charging and is not easily corroded. The positive electrode current collector 1A may be made of, for example, a metal such as aluminum, stainless steel, nickel, or titanium, or a conductive resin. The positive electrode current collector 1A may be in the form of a powder, a foil, a punched piece, or an expanded piece.
[0064] "Positive electrode mixture layer" The positive electrode mixture layer 1B contains a positive electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.
[0065] (Cathode active material) The positive electrode active material is not particularly limited as long as it can reversibly absorb and release, and insert and remove (intercalate and deintercalate) lithium ions. As the positive electrode active material, a positive electrode active material used in a known lithium ion secondary battery can be used. As the positive electrode active material, for example, lithium-containing metal oxide, lithium-containing metal phosphate, etc. can be mentioned.
[0066] The lithium-containing metal oxide is, for example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Lithium Manganese Spinel (LiMn 2 O 4 ), and general formula: LiNi x Co y Mn z O 2 The complex metal oxide represented by (x+y+z=1), lithium vanadium compound (LiVOPO 4 , Li 3 V 2 (PO 4 ) 3 ), olivine type LiMPO 4 (wherein M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li 4 Ti 5 O 12 ) etc.
[0067] The positive electrode active material may not contain lithium. Such a positive electrode active material may be a lithium-free metal oxide (MnO 2 , V 2 O 5 etc.), non-lithium-containing metal sulfides (MoS 2 etc.), lithium-free fluorides (FeF 3 , V.F. 3 When using a positive electrode active material that does not contain lithium, the negative electrode is doped with lithium ions in advance, or a negative electrode containing lithium ions is used.
[0068] (binder) The positive electrode mixture layer 1B may contain a binder. The binder bonds the positive electrode active material, the solid electrolyte, and the conductive assistant that constitute the positive electrode mixture layer 1B to each other. The binder also bonds the positive electrode mixture layer 1B to the positive electrode current collector 1A. The binder preferably has oxidation resistance and good adhesiveness.
[0069] Examples of the binder used in the positive electrode mixture layer 1B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or a mixture thereof. Among these, it is particularly preferable to use PVDF as the binder.
[0070] The content of the binder in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 5% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive assistant, and binder. If the amount of binder is too small, it tends not to be possible to form a positive electrode 1 with sufficient adhesive strength. Conversely, if the amount of binder is too large, it tends to be difficult to obtain sufficient volume or mass energy density, since general binders are electrochemically inactive and do not contribute to discharge capacity.
[0071] (solid electrolyte) The positive electrode mixture layer 1B may contain a solid electrolyte. The solid electrolyte is, for example, the above-mentioned solid electrolyte. When the above-mentioned solid electrolyte is used in the negative electrode 2 or the solid electrolyte layer 3, the solid electrolyte of the positive electrode 1 does not have to be the above-mentioned solid electrolyte. The content of the solid electrolyte in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1 vol.% or more and 50 vol.% or less, and more preferably 5 vol.% or more and 30 vol.% or less, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0072] (Conductive assistant) The conductive assistant improves the electronic conductivity of the positive electrode mixture layer 1B. Known conductive assistants can be used. The conductive assistant is, for example, a carbon material such as carbon black, graphite, carbon nanotubes, graphene, etc., a metal such as aluminum, copper, nickel, stainless steel, iron, or amorphous metal, a conductive oxide such as ITO, or a mixture thereof. The conductive assistant may be in the form of a powder or fiber.
[0073] The content of the conductive assistant in the positive electrode mixture layer 1B is not particularly limited. When the positive electrode mixture layer 1B contains the conductive assistant, the content is preferably 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 5% by mass or less, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0074] <Negative electrode> 1, the negative electrode 2 has a negative electrode current collector 2A and a negative electrode mixture layer 2B. The negative electrode mixture layer 2B is in contact with at least one surface of the negative electrode current collector 2A.
[0075] "Negative electrode current collector" The negative electrode current collector 2A may have electrical conductivity. For example, a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin foil may be used as the negative electrode current collector 2A. The negative electrode current collector 2A may be in the form of a powder, a foil, a punching, or an expandable material.
[0076] "Negative electrode mixture layer" The negative electrode mixture layer 2B contains a negative electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.
[0077] (Negative electrode active material) The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions and insert and extract lithium ions. As the negative electrode active material, any negative electrode active material used in a known all-solid-state battery can be used.
[0078] Examples of the negative electrode active material include carbon materials such as natural graphite, artificial graphite, mesocarbon microbeads, mesocarbon fibers (MCF), cokes, glassy carbon, and organic compound sintered bodies, Si, SiO x Metals that can combine with lithium, such as Sn and aluminum, their alloys, composites of these metals and carbon materials, lithium titanate (Li 4 Ti 5 O 12 ), SnO 2 and the like, metallic lithium, etc. The negative electrode active material is preferably natural graphite.
[0079] (binder) The negative electrode mixture layer 2B may contain a binder. The binder bonds the negative electrode active material, the solid electrolyte, and the conductive additive that constitute the negative electrode mixture layer 2B together. The binder also bonds the negative electrode mixture layer 2B and the negative electrode current collector 2A together.
[0080] Examples of the binder used in the negative electrode mixture layer 2B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or a mixture thereof. Among these, it is preferable to use one or more types selected from SBR, CMC, and PVDF as the binder.
[0081] The binder content in the negative electrode mixture layer 2B is not particularly limited, but is preferably from 1 mass % to 15 mass %, and more preferably from 1.5 mass % to 10 mass %, based on the total mass of the negative electrode active material, the conductive assistant, and the binder.
[0082] (solid electrolyte) The negative electrode mixture layer 2B may contain a solid electrolyte. The solid electrolyte is, for example, the above-mentioned solid electrolyte. When the above-mentioned solid electrolyte is used in the positive electrode 1 or the solid electrolyte layer 3, the solid electrolyte of the negative electrode 2 does not have to be the above-mentioned solid electrolyte. The content of the solid electrolyte is not particularly limited, but is preferably 1% by volume or more and 50% by volume or less, and more preferably 5% by volume or more and 30% by volume or less, based on the total mass of the negative electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0083] (Conductive assistant) The conductive assistant contained in the negative electrode mixture layer 2B may be the same as that in the positive electrode mixture layer 1B. The content of the conductive assistant in the negative electrode mixture layer 2B is preferably 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 12% by mass or less, relative to the negative electrode active material.
[0084] <Exterior body> The exterior body houses a battery element consisting of a positive electrode 1, a solid electrolyte layer 3, and a negative electrode 2. The exterior body prevents moisture and the like from entering from the outside to the inside. The exterior body is, for example, a metal laminate film made by coating both sides of a metal foil with a polymer film. The metal laminate film is formed into a bag shape and the opening is heat sealed to make the exterior body.
[0085] The metal foil is, for example, an aluminum foil, a stainless steel foil, etc. The polymer film arranged on the outside of the exterior body is preferably made of a polymer with a high melting point, such as polyethylene terephthalate (PET), polyamide, etc. The polymer film arranged on the inside of the exterior body is, for example, polyethylene (PE), polypropylene (PP), etc.
[0086] <External terminal> The external terminals include a positive electrode terminal and a negative electrode terminal. The positive electrode terminal is electrically connected to the positive electrode 1, and the negative electrode terminal is electrically connected to the negative electrode 2. The external terminals are made of a conductive material such as aluminum or nickel.
[0087] [Manufacturing method of all-solid-state batteries] First, the solid electrolyte according to this embodiment is produced by the method described above.
[0088] Next, the positive electrode 1 is prepared. The positive electrode 1 is produced by applying a paste containing a positive electrode active material onto a positive electrode current collector 1A and drying it to form a positive electrode mixture layer 1B. The above-mentioned solid electrolyte may be added to the paste containing the positive electrode active material.
[0089] Next, the negative electrode 2 is prepared. The negative electrode 2 is produced by applying a paste containing a negative electrode active material onto a negative electrode current collector 2A and drying it to form a negative electrode mixture layer 2B. The above-mentioned solid electrolyte may be added to the paste containing the negative electrode active material.
[0090] The battery element can be produced, for example, by powder molding. A guide with a hole is placed on the positive electrode 1, and the guide is filled with a solid electrolyte. The surface of the solid electrolyte is then smoothed, and the negative electrode 2 is placed on top of the solid electrolyte. This sandwiches the solid electrolyte between the positive electrode 1 and the negative electrode 2. Pressure is then applied to the positive electrode 1 and the negative electrode 2 to pressure-mold the solid electrolyte. By pressure molding, a laminate is obtained in which the positive electrode 1, solid electrolyte layer 3, and negative electrode 2 are stacked in this order.
[0091] Next, external terminals are welded to the positive electrode current collector 1A of the positive electrode 1 and the negative electrode current collector 2A of the negative electrode 2, which form the laminate, by a known method, to electrically connect the positive electrode current collector 1A or the negative electrode current collector 2A to the external terminal. Thereafter, the laminate connected to the external terminal is housed in an exterior body, and the opening of the exterior body is heat-sealed to seal it. Through the above steps, the all-solid-state battery of this embodiment is obtained.
[0092] The all-solid-state battery according to this embodiment has excellent initial charge-discharge efficiency because it contains a solid electrolyte of a predetermined composition. This is believed to be because the all-solid-state battery contains a solid electrolyte that satisfies a predetermined composition in which a part of Zr is replaced with Al. It is believed that Al has a lower reduction potential than Zr, widening the potential window of the solid electrolyte and improving the reduction resistance of the solid electrolyte. When the reduction resistance of the solid electrolyte is improved, the initial charge-discharge efficiency of the all-solid-state battery is increased.
[0093] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES
[0094] "Example 1" In a glove box with a dew point of approximately -75°C, AlCl 3 and ZrCl 4 and Li 2O was weighed at a predetermined molar ratio. Next, the raw material powder was put into a zirconia sealed container for a planetary ball mill in which zirconia balls of 5 mmΦ had been placed in advance. Next, the sealed container was covered, the lid was screwed onto the container body, and the gap between the lid and the container was sealed with polyimide tape. The polyimide tape has the effect of blocking moisture. Next, the zirconia sealed container was set in a planetary ball mill. The rotation speed was 330 rpm, the revolution speed was 330 rpm, and the rotation direction and the revolution direction were reversed to each other, and a mechanochemical reaction was performed for 24 hours. Then, the composition of the prepared solid electrolyte was analyzed by surface analysis using an electron beam microanalyzer (EPMA), and the composition of the solid electrolyte was confirmed. The prepared solid electrolyte was also subjected to X-ray diffraction measurement using Cu-Kα radiation. In the solid electrolyte of Example 1, peaks were confirmed in the first and third ranges, but no peak was confirmed in the second range. Therefore, the second intensity of the solid electrolyte of Example 1 was zero.
[0095] [Measurement of ionic conductivity] Next, in a glove box with argon gas circulating at a dew point of approximately -70°C, the solid electrolyte powder was filled into a pressure molding die and pressure molded under a load of approximately 30 KN to prepare a measurement cell for ionic conductivity.
[0096] The pressure molding die is composed of a PEEK (polyether ether ketone) cylinder with a diameter of 10 mm, and upper and lower punches made of SKD11 material with a diameter of 9.99 mm.
[0097] After that, a stainless steel disk and a Teflon (registered trademark) disk, both 50 mm in diameter and 5 mm thick with four screw holes, were prepared and the pressure molding die was set as follows. They were loaded in the following order: stainless steel disk / Teflon (registered trademark) disk / pressure molding die / Teflon (registered trademark) disk / stainless steel disk, and the four screws were tightened with a torque of approximately 3 N m. Screws were also inserted into the screw holes on the sides of the upper and lower punches to serve as external connection terminals.
[0098] The external connection terminal was connected to a potentiostat (VersaSTAT3 manufactured by Princeton Applied Research) equipped with a frequency response analyzer, and the ionic conductivity was measured using an impedance measurement method. The measurement was performed at a measurement frequency range of 1 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 25°C. The ionic conductivity of the solid electrolyte of Example 1 was 0.10 mS / cm.
[0099] [Charge / discharge evaluation] The charge and discharge were evaluated for each of the negative electrode half-cell and the positive electrode half-cell.
[0100] The negative half-cell was fabricated as follows. In a glove box, 80 mg of solid electrolyte was pressed at 0.6 tons for 1 minute. This solid electrolyte was LPSC (Li 6 P.S. 5 Cl). Then, 10 mg of the negative electrode mixture was added to one side of the pressed solid electrolyte, and pressed at a pressure of 0.6 tons for 1 minute, and then pressed at a pressure of 3 tons for 1 minute. The negative electrode mixture contains a negative electrode active material, a solid electrolyte, and a conductive additive in a ratio of 60 parts by mass: 35 parts by mass: 5 parts by mass. The negative electrode active material is lithium titanate (Li 4 Ti 5 O 12 ) The solid electrolyte contained in the negative electrode was the solid electrolyte prepared by the above procedure. Carbon black was used as the conductive assistant. Li foil was placed on the surface of the solid electrolyte opposite to the surface on which the negative electrode composite was laminated. These were restrained at 3 Nm using a restraining jig and sealed in an aluminum pouch with terminals. In this manner, a negative electrode half cell for charge / discharge evaluation was prepared. This negative electrode half cell contains the above-mentioned solid electrolyte as the solid electrolyte contained in the negative electrode composite.
[0101] The positive electrode half-cell was fabricated as follows. In a glove box, 30 mg of the above solid electrolyte and LPSC (Li 6 P.S. 5The positive electrode mixture was added to one side of the pressed solid electrolyte, and pressed at a pressure of 0.6 tons for one minute, followed by a final pressing at a pressure of 3 tons for one minute. The positive electrode mixture contained a positive electrode active material, a solid electrolyte, and a conductive additive in a ratio of 60 parts by mass:35 parts by mass:5 parts by mass. The positive electrode active material was lithium cobalt oxide (LiCoO 2 ) The solid electrolyte contained in the positive electrode was also prepared by the above procedure. Carbon black was used as the conductive assistant. Li foil was placed on the surface of the solid electrolyte opposite to the surface on which the positive electrode composite was laminated. These were restrained at 3 Nm using a restraining jig and sealed in an aluminum pouch with terminals. In this manner, a positive electrode half cell for charge / discharge evaluation was prepared. This positive electrode half cell contains the above-mentioned solid electrolyte as part of the solid electrolyte contained in the positive electrode composite and the solid electrolyte contained in the solid electrode layer.
[0102] Next, the negative electrode half cell and the positive electrode half cell were each charged and discharged in a temperature environment of 25° C. The charge and discharge rates were set to 0.05C (the current value at which charging or discharging is completed in 20 hours when charging or discharging at a constant current of 1 mA is performed at 25° C.), and a charge and discharge test was performed. Charging was performed at a constant current and voltage up to 2.5V, and discharging was performed up to 1.3V.
[0103] "Examples 2 to 11" Examples 2 to 11 differ from Example 1 in that the raw material ratio and the mixing conditions of the mechanochemical treatment when preparing the solid electrolyte were changed (except for Examples 4 and 11). 2 Fixed molar ratio of O and AlCl 3 and ZrCl 4The molar ratio of was changed. The solid electrolytes of Examples 2 and 3 were subjected to a mechanochemical reaction at a rotation speed of 3 rpm to 5 rpm and a revolution speed of 200 rpm to 250 rpm for 24 hours to 48 hours. The other conditions were the same as in Example 1, and the same evaluation was performed. The solid electrolytes of Examples 2 and 3 did not have a peak in any of the first range, the second range, and the third range in the X-ray diffraction pattern using Cu-Kα radiation, and therefore satisfied the second condition. The solid electrolytes of Examples 5 to 10 had a peak in any of the first range, the second range, and the third range in the X-ray diffraction pattern using Cu-Kα radiation, and therefore satisfied the first condition. The solid electrolytes of Examples 2 and 3 did not have a peak in the second range in the X-ray diffraction pattern using Cu-Kα radiation, and therefore satisfied the first condition.
[0104] "Examples 12 to 19" Examples 12 to 19 differ from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed, lithium halide or zirconium halide was further added to the raw materials when preparing the solid electrolyte, and the mixing conditions for the mechanochemical treatment were changed. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0105] "Examples 20 to 23" Examples 20 to 23 differ from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed and the mixing conditions for the mechanochemical treatment were changed. 3 and ZrCl 4 The molar ratio of Li is fixed. 2 The molar ratio of O was changed. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0106] "Examples 24 to 27" Examples 24 to 27 differ from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed, zirconium oxide or aluminum oxide was further added to the raw materials when preparing the solid electrolyte, and the mixing conditions for the mechanochemical treatment were changed. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0107] "Examples 28 and 29" Examples 28 and 29 differ from Example 5 in that a two-stage synthesis method was used to prepare the solid electrolyte, and the mixing conditions of the mechanochemical treatment were changed. By synthesizing the solid electrolyte in two stages, oxide particles were confirmed in the solid electrolyte. Examples 28 and 29 differ in the particle size of the oxide particles. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0108] "Examples 30 to 46" Examples 30 to 46 differ from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed, the chloride of G was further added to the raw material when preparing the solid electrolyte, and the mixing conditions for the mechanochemical treatment were changed. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0109] "Comparative Examples 1 to 8" Comparative Example 1 differs from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed, lithium chloride was further added, and the mixing conditions for the mechanochemical treatment were changed. Comparative Examples 2 to 5 differ from Example 1 in that the raw material ratios used in producing the solid electrolyte were changed, and the mixing conditions for the mechanochemical treatment were changed (except for Comparative Example 5). In Comparative Example 6, AlCl was used as a raw material for producing the solid electrolyte. 3 This differs from Example 1 in that no. Comparative Examples 7 and 8 are different from Example 1 in that the raw material ratio when preparing the solid electrolyte was changed, and the mixing conditions of the mechanochemical treatment were changed. In Comparative Examples 7 and 8, the mixing conditions of the mechanochemical treatment were a rotation speed of 1 rpm, a revolution speed of 280 rpm, and a reaction time of 24 hours. The solid electrolytes of Comparative Examples 7 and 8 had peaks in the first, second, and third ranges in the X-ray diffraction patterns using Cu-Kα rays, but did not satisfy the first condition. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0110] The conditions and the measurement results of Examples 1 to 46 and Comparative Examples 1 to 8 are summarized in the following table. In the column of oxide particles in the following table, "○" means that oxide particles were confirmed, and "×" means that oxide particles were not confirmed. In the following table, "ND" means that the ion conductivity was too low to be measured. In the following table, I2 / I1 is the first intensity ratio, and I3 / I2 is the second intensity ratio. Each of Examples 1 to 46 had a higher initial charge-discharge efficiency than each of Comparative Examples 1 to 8.
[0111] [Table 1]
[0112] [Table 2]
[0113] [Table 3]
[0114] [Table 4]
[0115] [Table 5]
[0116] [Table 6]
[0117] "Example 47" Example 47 is the Li 2 NaO 2 The difference from Example 1 is that the conductive ion of the solid electrolyte of Example 47 is changed to Na. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0118] "Examples 48 to 57" Examples 48 to 57 differ from Example 47 in that the raw material ratios used in preparing the solid electrolyte were changed. 2 Fixed molar ratio of O and AlCl 3 and ZrCl 4 The other conditions were the same as in Example 47, and the same evaluation was performed.
[0119] "Examples 58 to 65" Examples 58 to 65 differ from Example 47 in that the raw material ratios when preparing the solid electrolyte were changed, and sodium halide or zirconium halide was further added to the raw materials when preparing the solid electrolyte. The other conditions were the same as in Example 47, and the same evaluation was performed.
[0120] "Comparative Examples 7 to 10" Comparative Example 7 differs from Example 47 in that the raw material ratio in producing the solid electrolyte was changed and sodium chloride was further added. Comparative Examples 8 and 9 differ from Example 47 in that the raw material ratios used in producing the solid electrolyte were changed. In Comparative Example 10, AlCl was used as the raw material for producing the solid electrolyte. 3 The difference from Example 47 is that no was used. The other conditions were the same as in Example 1, and the same evaluation was performed.
[0121] The conditions and measurement results of Examples 47 to 65 and Comparative Examples 7 to 10 are summarized in the following table. Each of Examples 47 to 65 had a higher initial charge-discharge efficiency than each of Comparative Examples 7 to 10.
[0122] [Table 7]
[0123] [Table 8]
[0124] [Table 9]
[0125] [Table 10] [Explanation of symbols]
[0126] 1... positive electrode, 1A... positive electrode current collector, 1B... positive electrode mixture layer, 2... negative electrode, 2A... negative electrode current collector, 2B... negative electrode mixture layer, 3... solid electrolyte layer, 10... all-solid-state battery
Claims
1. A a A b Zr 1-b+α G c O d X e ... is expressed as (1), In formula (1), A is at least one selected from the group consisting of Li, K, and Na; G is one or more selected from the group consisting of Mg, Ca, Sr, Ba, Y, Yb, Sc, La, Ce, Hf, Ta, W, and Nb; X is at least one selected from the group consisting of F, Cl, Br, and I; a satisfies 0.1<a<2+b+β, b satisfies 0.1≦b≦0.9, c satisfies 0≦c<0.5, d satisfies 0.01<d<3, e satisfies 2.5<e<6.1, α satisfies −0.5<α<0.3, β is When G is a pentavalent element, it satisfies −c and b>c+0.01; G is a tetravalent element or 0 when no G is present; When G is a trivalent element, it is c. When G is a divalent element, it is 2c. The X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation satisfies the first condition or the second condition, the first condition is a condition that a first intensity ratio obtained by dividing the second intensity by the first intensity and a second intensity ratio obtained by dividing the second intensity by the third intensity are both equal to or less than 2.0; the first intensity is a maximum diffraction intensity in a first range of a diffraction angle of 29.5°±0.5°; the second intensity is a maximum diffraction intensity in a second range of a diffraction angle of 31.9°±0.5°, the third intensity is a maximum diffraction intensity in a third range of a diffraction angle of 34.6°±0.5°, The second condition is a condition that there is no peak in the first range, the second range, or the third range. solid electrolyte.
2. The solid electrolyte according to claim 1 , wherein in the formula (1), X contains Cl.
3. 2. The solid electrolyte according to claim 1, wherein, in the formula (1), X includes any one or more selected from the group consisting of Cl, F, Br, and I.
4. The solid electrolyte according to claim 1 , wherein in the formula (1), X is Cl.
5. The solid electrolyte according to claim 1 , wherein in the formula (1), A is Li.
6. The solid electrolyte according to claim 1 , wherein in the formula (1), A is Na.
7. The solid electrolyte according to claim 1 , wherein in the formula (1), a satisfies 0.5<a<2+b+β.
8. The solid electrolyte according to claim 1, wherein, in the formula (1), b satisfies 0.3≦b≦0.7, and 1+α+c satisfies 0.8<1+α+c<1.
2.
9. The solid electrolyte according to claim 1 , wherein, in the formula (1), c satisfies 0≦c≦0.
3.
10. Further comprising oxide particles, 2. The solid electrolyte according to claim 1, wherein the oxide particles have a particle size of 5.0 μm or less.
11. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The negative electrode comprises the solid electrolyte according to any one of claims 1 to 10.
12. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The solid electrolyte layer comprises the solid electrolyte according to any one of claims 1 to 10.
13. A positive electrode, a negative electrode, and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode, The positive electrode comprises the solid electrolyte according to any one of claims 1 to 10.
Citation Information
Patent Citations
Solid electrolyte, solid electrolyte layer, and solid electrolyte cell
WO2021024785A1
Cited By
High-valence cation doped amorphous dominant halide solid electrolyte as well as preparation method and application thereof
CN122474687A